Brain-spine interface: A promising technology to improve mobility in spinal cord injuries - Vera Cuya, Ronald Martin (2024)
Located in the lumbar and cervical regions of the spinal cord are the neurons that produce leg and arm movements. Reactivation of these neurons can be achieved by applying epidural electrical stimulation (EES) to these specific regions. There is evidence to support the claim that EES directly recruits large diameter afferent fibres at the point of entry into the spinal cord via the dorsal roots. Recruitment of the large afferent fibres results in the activation of motor neurons in the spinal segment connected to the root where these afferents are located. By activating certain dorsal roots, it becomes feasible to regulate muscle groups, considering that the motor neurons for the extensor and flexor muscles of each joint are located in separate segments of the spinal cord.